SINONIM NOMINA BAHASA DAYAK KANAYATN DIALEK BADAMEA - Wulandari, Fitaloka; Syahrani, Agus; Muzammil, Ahmad Rabi’ul (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
Abstract This study was conducted in Malabae of Marunsu Village, Samalantan District of Bengkayang Regency. The researcher involved two speakers as the informants to collect the data related to the synonyms of nouns in Dayak Kanayatn language of Badamea dialect. This study focuses on determining distinguishing features of meaning from a set of synonymous nouns and their use in the Dayak Kanayatn dialect of Badamea. The method used in conducting this study was descriptive in the form of qualitative research. The data were collected from the informants in the form of the synonymous nouns of Kanayatn language with the Badamea dialect. The techniques applied to collect the data were interviews, recording, and note-taking. The findings showed several lists of synonymous nouns: (1) pairs of synonymous nouns related to humans (2) pairs of synonymous nouns related to concrete non-animate nouns and (3) pairs of synonymous nouns related to abstract non-animate nouns. Those pairs of nouns have differences in their usage context, and thus they are only close synonyms. Keywords: Synonymous Nouns, Dayak Kanayatn Language, Badamea dialects